CONHECIMENTOS DIDÁTICO-MATEMÁTICOS DO PROFESSOR DE MATEMÁTICA PARA O ENSINO DE NÚMEROS RACIONAIS - Carpes, Patricia Pujol Goulart (2019)
The knowledge that involves the work of the Mathematics teacher when teaching his classes should take into account different dimensions according to the perspective of the modular system CDM (Didactic-Mathematical Knowledge – DMK in English) developed by Godino and collaborators, which interprets and organizes the teacher's knowledge from of three dimensions, namely: mathematical dimension, didactic dimension and meta didactic-mathematical dimension. The present study aims investigate the development of Didactic-Mathematical Knowledge about rational numbers in a group of Mathematics teacher based on system CDM. For this, we organized a training and investigative course with mathematics teachers from the municipal schools of Itaqui (RS) dealt with the mathematical object "rational number" for the final years of elementary school. The course was organized in nine face-to-face and sequential meetings, totaling 36 hours and discussed the teacher's didactic-mathematical knowledge by specifically teaching the theme and using portfolios built by the teachers. The qualitative research had its data were analyzed from the Guide to Evaluate the Didatic Suitability of Mathematical Education Instruction Processes (GVID-IDM) which points out components and indicators to analyze and evaluate teacher education courses by the dimensions of the CDM and that is based on the EOS (Onto-Semiotic Approach – OSA in English) of Godino and collaborators. The data indicate that teachers have little familiarity in the transit between meanings of rational numbers and their representations. In addition, they are unfamiliar with the Problem Solving methodology. The portfolios built by the teachers during the training course served as a guide for the proposed formation, to organize the teachers' activities / thinking, and orientate the interactions and the exchange of experiences between the teachers and students in the classroom environment. They also provided a reflection / support on the knowledge mobilized on rational numbers. The activities developed in the course were focused on teacher preparation and referrals to elucidate recurring student doubts or epistemic and cognitive conflicts. Finally, we consider that the coherent and systemic articulation of the dimensions, in this process of continuous formation of Mathematics teachers, reveals itself as a favorable environment for the improvement of teachers' didactic-mathematical knowledge. Beyond this is a theory that supports and guides a proposal for teaching and learning rational numbers for the final years of elementary school.